2021
DOI: 10.3329/jemc.v10i2.53533
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity among Medical Students of Enam Medical College, Savar, Dhaka

Abstract: Background: Overweight and obesity are recognized as “escalating epidemics” affecting both developed and developing countries. Of the factors contributing to obesity, stress seems to be particularly important as stressful condition leads to irregularity in diet, lack of exercise and addiction. Medical students are exposed to a lot of stress throughout their education. Hence, this study was undertaken to find out the prevalence of overweight and obesity among undergraduate medical students. Objectives: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…In our study, there is a statistically significant association between a positive family history of overweight and obesity and overweight and obesity in the present study (P=0.001). Similar to ours, studies conducted by Baruah et al, 20 and Begum et al, 21 concluded that there is a significant association between a positive family history of overweight and obesity and overweight and obesity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, there is a statistically significant association between a positive family history of overweight and obesity and overweight and obesity in the present study (P=0.001). Similar to ours, studies conducted by Baruah et al, 20 and Begum et al, 21 concluded that there is a significant association between a positive family history of overweight and obesity and overweight and obesity.…”
Section: Discussionsupporting
confidence: 90%
“…The study conducted by Baruah et al, 20 and Begum et al, 21 concluded that there is no significant association between family history of hypertension and overweight and obesity, which was the case in the present study. In contrast, a study conducted by Basu M et al, 22 concluded that there was a significant association between family history of diabetes and hypertension and overweight and obesity.…”
Section: Discussionsupporting
confidence: 51%